Healthy lifestyle interventions : a systematic review from a realist perspective - Voss, Miranda (Department of Public Health and Family Medicine, 2014)
This thesis is a systematic review using realist methodology. It emerged out of an original protocol that proposed an exploration of the barriers to a healthy lifestyle in poorer peri-urban communities. The purpose of that protocol was to design more effective lifestyle interventions, and participatory action research was identified as a potentially effective methodology to encourage behaviour change in contexts where self efficacy may be low. That development itself raised questions about what exactly was meant by action research, participatory action research and community based participatory methodologies and how effective they were. Given these questions, it was decided to undertake a systematic review of published literature and it is that review that is presently submitted as a thesis.